Experiencing modernization: frontline probation perspectives on the transition to a National Offender Management Service - Robinson, G; Burnett, R (SAGE Publications, 2007)
The National Offender Management Service (NOMS), intended to integrate the Probation and Prison Services of England and Wales and to provide an operational framework for the end-to-end management of offenders throughout their sentences, was introduced in summer 2004. This major innovation came fast after a period of immense change to probation services which had culminated in the formation of the National Probation Service (NPS) in 2001. The present study, in which 41 probation practitioners from four probation areas were interviewed, sought to gain insight into frontline perspectives on the impact of NOMS. The study indicates that communication to frontline staff about NOMS had not been wholly effective and many practitioners are experiencing 'initiative confusion' and 'change fatigue' in endeavouring to meet an increasing range of demands from an expanding range of 'masters'. While many remain open to the possible benefits of NOMS, particularly for offenders, considerable uncertainty remains about the implications of NOMS for themselves and the Probation Service. The 'ogre of contestability' is linked with fears about future job security, while other aspects of the NOMS agenda are adding to a sense of demoralization and increasing alienation from the values that brought some into the service.